2010
DOI: 10.1016/j.bpj.2009.12.2038
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Melatonin's Multiple Mitochondrial Levels of Protection Against Mitochondrial Ca2+-Mediated Permeability Transition and Beyond in Rat Brain Astrocytes

Abstract: concentrations (30-500 mM) inhibited this activity. Acute exposure of control cf-EPC to 100 mM MGO increased basal cytoplasmic Ca 2þ and this was followed by an increased production of mitochondrial superoxide. These new data suggest that MGO whose production is increased shortly after the onset of hyperglycemia is inducing cf-EPC demise by mechanisms that involve perturbations in intracellular calcium homeostasis and increased production of mitochondrial superoxide. Overexpression of glyoxalase 1 minimizes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(120 citation statements)
references
References 0 publications
6
114
0
Order By: Relevance
“…Another interesting aspect of melatonin is that it is taken up by mitochondria, providing in situ protection against oxidative damage [146,147]. Several reports have shown that melatonin improves mitochondrial function, reduces mitochondrial oxidative status, and increases the activity of the respiratory chain [146,148].…”
Section: Function As a Free Radical Scavengermentioning
confidence: 99%
“…Another interesting aspect of melatonin is that it is taken up by mitochondria, providing in situ protection against oxidative damage [146,147]. Several reports have shown that melatonin improves mitochondrial function, reduces mitochondrial oxidative status, and increases the activity of the respiratory chain [146,148].…”
Section: Function As a Free Radical Scavengermentioning
confidence: 99%
“…As a matter of fact, previous studies indicate that melatonin is neuroprotective in streptozotocin-induced rat model of diabetic neuropathy [104] . Once again, it would appear that the quenching of free radicals by melatonin might be the central mechanism for exerting neuroprotection [105,106] , although other melatonin-induced neuroprotective mechanisms cannot be ruled out. Thus, recent evidence in an experimental model of diabetic neuropathy suggests that melatonin modulates neuroinflammation by inhibiting the NF-κB pathway and downstream mediators of inflammation, and protects against oxidative stress by upregulating the nuclear erythroid 2-related factor 2 (Nrf2) pathway, thereby contributing to melatonin's neuroprotective effect [107] .…”
Section: Melatonin Modulates Diabetes-related Alterationsmentioning
confidence: 99%
“…Melatonin is a special class of antioxidant because when scavenging free radicals, it becomes in a series of metabolites that are also free radical scavengers (Hardeland et al 2009). Melatonin is taken up by mitochondria ), providing an in situ protection against oxidative damage (Acuna et al 2002(Acuna et al , 2011Acuna-Castroviejo et al 2007;Jou et al 2010;Lopez et al 2009;Paradies et al 2010). Under physiological and pathological conditions, the ability of melatonin to maintain mitochondrial homeostasis has been reportedly showed (Acuna et al 2011;Acuna-Castroviejo et al 2001;Escames et al 2007;Lopez et al 2006a, b).…”
Section: Mitochondrial Dna Alterations In Acute Inflammatory Diseasesmentioning
confidence: 99%